2020
DOI: 10.2196/20472
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Digital Divides in Posting COVID-19 Content on Social Media Among US Adults: Secondary Survey Analysis

Abstract: Background Public health surveillance experts are leveraging user-generated content on social media to track the spread and effects of COVID-19. However, racial and ethnic digital divides, which are disparities among people who have internet access and post on social media, can bias inferences. This bias is particularly problematic in the context of the COVID-19 pandemic because due to structural inequalities, members of racial and ethnic mino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 43 publications
1
51
0
1
Order By: Relevance
“…The use of mHealth tools for COVID-19 education, risk reduction, and symptom monitoring may complement existing prevention strategies [ 98 ]. Our findings also highlight potential opportunities for mHealth tools to reduce racial/ethnic and age disparities in COVID-19 exposure and outcomes [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 87%
“…The use of mHealth tools for COVID-19 education, risk reduction, and symptom monitoring may complement existing prevention strategies [ 98 ]. Our findings also highlight potential opportunities for mHealth tools to reduce racial/ethnic and age disparities in COVID-19 exposure and outcomes [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 87%
“…While two prior HINTS studies have explored associations between internet use and vitamin/medication purchases [ 63 , 64 ], neither examined racial and ethnic differences, making this a novel finding. While a recent HINTS study did not observe racial/ethnic disparities in social media use [ 14 , 51 , 65 ], the study focused on use of specific social media, such as Facebook and Twitter, rather than broader online social networking platforms. We also observed a novel finding examining differences in online healthcare use by nativity status.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence documenting the effectiveness of internet-based interventions in improving chronic disease outcomes and the wealth of health information available, access and uptake of health information remains a challenge, thus potentially increasing health disparities across race/ethnicity, socioeconomic status, and language [ 12 , 13 , 14 , 15 , 16 ]. In particular, studies have observed gaps in internet use for specific health outcomes (e.g., cancer, cardiovascular disease) across race/ethnicity, age, and gender [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media is significantly more popular among individuals aged 15À29 years, and only 7% of Twitter users in the United States are aged 65 years [9]. Furthermore, older adults generate a limited amount of online content, with a recent study showing that older social media users, and particularly those who are frail or have disabilities, are less likely to post about COVID-19 (OR 0¢73) [10].…”
mentioning
confidence: 99%